Forecasting Stock Price Using Armax-Garchx Model During The Covid-19 Pandemic - Parwati, Lusiana Sani; Nugrahani, Endar Hasafah; Budiarti, Retno (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The Covid-19 pandemic, which was proclaimed by the World Health Organization (WHO) on March 2020, has impacted stock risk on the capital market. Stock price forecasting can be used to provide future stock projection prices in order to reduce risk. The ARMA GARCH model and its development model can forecast stock prices by incorporating exogenous factors such as the ARMAX GARCH, ARMA GARCHX, and ARMAX GARCHX models. PT Mitra Keluarga Karyasehat Tbk's stock price is analyzed in this study, along with the exogenous factors of total daily positive cases and total daily fatalities cases of Covid-19 from March 16, 2020, to January 31, 2022.The results of several models show that based on MAPE value the ARMAX GARCH model has better accuracy in forecasting stock price.